EJERCICIOS DE PATINAJE SOBRE RUEDA COMO DESARROLLO FÍSICO EN LOS NIÑOS DE 10 AÑOS DE EDAD DE LA COMUNIDAD VOLUNTAD DE DIOS DEL CANTÓN VINCES - LIBERIO CASQUETE MELANIE SUYIN (2024)
The objective of this study was to evaluate the impact of roller-skating exercises on the physical development of 10-year-old children from the Will of God community of the Vinces canton. For this, a methodology was used that was a pre-experimental design with a intervention group (children who will participate in regular skating sessions) and a control group (children who will not participate in the skating program). The evaluations were carried out before and after the exercise system to measure improvements in the aforementioned physical variables. The physical development of the children was evaluated at the beginning and at the end of the study, measuring variables such as balance, coordination, agility, muscular strength and cardiovascular resistance. The sample was composed of 32 boys and girls from the 14 male community, which represents the 43.75% and 18 are female, which represents 56.25%. Within the main results, after the intervention, the group that practiced roller skating showed significant improvements in balance (p<0.05), coordination (p<0.05), agility (p<0.05) and muscle strength (p<0.05). ) compared to the control group. No significant differences in cardiovascular endurance were observed between the groups. The exercise system applied had a positive and statistically significant impact on the physical performance of the participants in multiple areas, which highlights the effectiveness of the system to comprehensively improve the physical condition of the sample.